Trapezius muscle activity variation during computer work performed by individuals with and without neck-shoulder pain. - Kelson, Denean M.; Mathiassen, Svend Erik; Srinivasan, Divya (Applied Ergonomics, 2019)
This study aimed at determining the extent to which individuals with neck-shoulder pain and non-symptomatic individuals differ in muscle activation patterns, when performing computer work, as quantified by exposure variation analysis (EVA). As a secondary aim, we also aimed to quantify the day-to-day reliability of EVA variables describing trapezius muscle activation in a non-symptomatic control group. Thirteen touch-typing computer users (pain: n = 5, non-symptomatic: n = 8) completed three pre-selected computer tasks in the laboratory. Upper trapezius muscle activity was recorded using electromyography and analyzed using EVA with five amplitude and five duration categories. Individuals with neck-shoulder pain spent less time at low amplitudes and exhibited longer uninterrupted periods of muscle activation compared to their non-symptomatic counterparts. Thus, non-symptomatic workers tended to switch between exposure levels more often than individuals with pain. For a majority of EVA variables, ICCs ranged from 0.6 to 0.9, and between-days coefficients of variation were between 0.4 and 2.2.